2018
DOI: 10.32493/keberlanjutan.v2i2.y2017.p564-588
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP LIKUIDITAS PADA PT. ULTRAJAYA MILK INDUSTRY DAN TRADING COMPANY, Tbk.

Abstract: The purpose of this research is to know the rotation of receivable at similar company of industry (Milk Management), to know the cash turnover in similar company of industry (Milk Management), and to know how big influence of receivable turnover and cash turn over to liquidity in similar industry Milk Management). The method of research conducted by the author in preparing the thesis is descriptive quantitative, which is doing research that describes the financial condition of the company expressed in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
1
1
3
Order By: Relevance
“…This is the same as the results of research conducted by Simamora (2007) and Nur (2008) which show that partially, accounts receivable turnover has a significant effect on liquidity. But contrary to the results of research conducted by Lestari (2016) and Indriani (2017) that receivables turnover has no significant effect on liquidity.…”
Section: Introductioncontrasting
confidence: 80%
“…This is the same as the results of research conducted by Simamora (2007) and Nur (2008) which show that partially, accounts receivable turnover has a significant effect on liquidity. But contrary to the results of research conducted by Lestari (2016) and Indriani (2017) that receivables turnover has no significant effect on liquidity.…”
Section: Introductioncontrasting
confidence: 80%
“…Meanwhile, Sriwalet, Sianturi, & Rajaguguk (2019) stated that cash flow had a significant negative effect on the current ratio. In line with that, it was found that cash turnover partially had a positive and significant effect on company liquidity (Lestari, 2017). Through these previous studies, the following research hypothesis is developed.…”
Section: Effect Of Cash Turnover On Liquiditymentioning
confidence: 64%
“…Investasi yang terkesan terjadi pertumbuhan serta berkembang pesat yang nantinya memungkinkan jadi motor penggerak suatu perekonomian. Menurut (Lestari & Rusnaeni, 2013) menyatakan bahwa periode berputarnya kas yang dimulai pada saat kas diinvestasikan dalam komponen modal kerja sampai saat kembali menjadi kas sebagai unsur modal kerja yang paling tinggi likuiditasnya, sedangkan (Nugroho et al, 2019) menyebutkan untuk menjaga kemampuan likuiditas perusahaan, maka perusahaan harus harus dapat mengelola jumlah kas yang dimiliki.…”
Section: Pendahuluanunclassified
“…(Mulyanti & Supriyani, 2018) untuk mendapatkan kas yang cukup dalam jumlah tertentu perusahaan harus memaksimalkan perputaran kasnya. Kas yang merupakan bagian dari unsur capital yang penting dan yang memiliki tingkat likuid yang tinggi, maka perputaran kas merupakan pencapaian periode kas dari awal kas di kelola hingga kas itu kembali (Lestari & Rusnaeni, 2013). Nilai kas yang cukup banyak mencerminkan Likuiditas suatu perusahaan tersebut tinggi, hal ini berarti terjadi kelebihan kas sehingga perputaran kas rendah.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation